Association of serum total bilirubin level with severity of coronary atherosclerosis is linked to systemic inflammation. Issue 1 (May 2015) - Akboga, Mehmet Kadri; Canpolat, Ugur; Sahinarslan, Asife; Alsancak, Yakup; Nurkoc, Serdar; Aras, Dursun; Aydogdu, Sinan; Abaci, Adnan
Abstract Objective Although cardiovascular protective action of bilirubin has been attributed to its antioxidant effect, there was scarce data regarding the anti-inflammatory properties. Herein, we aimed to assess the relationship between serum total bilirubin level and severity of coronary artery disease (CAD) in association with the direct inflammatory marker such as C-reactive protein (CRP), the other indirect markers included in inflammation process such as neutrophil to lymphocyte ratio (NLR) and red cell distribution width (RDW) in patients with stable CAD. Methods Angiographic data of 1501 patients were analyzed in this retrospective cross-sectional study. Patients were categorized according to Gensini scores as control, mild CAD and severe CAD groups. The association of clinical and laboratory parameters with the severity of CAD were determined by multivariable linear regression analysis. Results Total bilirubin level in the control group was significantly higher than those of the other groups. After multivariable linear regression analysis total bilirubin [β = −3.131 (−4.481, −1.782), p < 0.001] was significantly associated with the severity of CAD. Futhermore, there was a moderate and significant inverse correlation between serum total bilirubin level and the severity of CAD (r = −0.173, p < 0.001), CRP (r = −0.112, p < 0.001), NLR (r = −0.070, p = 0.026) and RDW (r = −0.074, p = 0.027). Conclusion Serum total bilirubin level was independently and inversely associated with the severity of coronary atherosclerosis in patients with stable CAD. In addition, total bilirubin level was inversely correlated with CRP, NLR and RDW. These results suggest that besides its already known effect on the oxidative stress, higher serum total bilirubin level may exhibit an anti-inflammatory effect in the coronary atherosclerotic process.